PENGARUH PERSEPSI MANFAAT, KEAMANAN DAN KEMUDAHAN TERHADAP MINAT NASABAH MENGGUNAKAN LAYANAN MOBILE BANKING PADA PT. BANK SYARIAH INDONESIA DI TANGERANG - Junaedi, Edy; Neneng , Neneng (Islamic Banking & Economic Law Studies (I-BEST), 2023)
This study aims to investigate the effect of benefits, safety and convenience on customers' interest in using Mobile Banking. The growth of transactions on BSI mobile has increased very rapidly during the Covid-19 pandemic from March 2020 to July 2021, the number of mobile banking users is 2.5 million users with BSI mobile transaction growth of 46.4 million transactions, up to 97.4 %. The increase in mobile BSI transactions was driven by the presence of new habits from Indonesian people during the Covid-19 pandemic and customer financial transaction activities in shopping on e-commerce The research method by collecting data using research questionnaires and data processing using SPSS version 22 The benefits variable has a coefficient value of 0.76, has a positive effect on interest with a significant value of 0.02. The security variable has a coefficient value of 0.169, the Security Perception variable has a positive effect on interest, but not significant with a value of 0.162. The convenience variable gives a coefficient value of .464. Ease has a positive and significant effect of .000 on the interest in using mobile banking. The results of the F count show the number 74.210 and a significant value of 0.000, which is less than the value of 0.5. This means that the independent variables simultaneously or simultaneously affect the dependent variable.